Potensi Pengembangan Transportasi Publik Terpadu Antar Kawasan Kota Baru di Tangerang Raya - Mawarni, Ida Ayu Sawitri Dian; Wikanto, Elya (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
The large number of new towns development in Tangerang Raya has risen a lot of potential as well as problems. The continued growth of population in new towns has segregated Tangerang area into city centers concentrated with each development. This research focused on the lanes from Boulevard Gading Serpong to BSD Raya Utama which connect new city areas and divide the north-south segments of Jakarta-Merak toll road to Serpong - Balaraja toll road. These lanes have good prospect to develop an integrated transportation system. This study aims to identify the prospect of an integrated transportation development of the new town areas in Tangerang Raya. The method used in this study by conducting a literature study and survey of road users’ preferences. The analysis model used superimposed analysis by overlaying maps of variable analysis to see the magnitude of the roads importance to develop an integrated public transportation system. The results show that the adequate population density, the ability of the road corridor to connect urban centers, the high density of vehicles along the corridor, and the prospect to develop infrastructure and other modes of transportation in the vicinity, are factors that create these road corridors suit to be developed as an integrated public transportation